Philosophy and education between Bacon and Descartes - Jassim, Zahraa; Al-Muhammadawi, Ali (Al-Adab Journal, 2024)
The topic of education is one of the topics that has occupied the attention of many researchers, thinkers, and philosophers. This research addresses the topic of “philosophy and education” according to both the English philosopher Francis Bacon (1561-1626 AD) and the French philosopher Rene Descartes (1596-1650 AD), And to show the extent of the impact of educational philosophy on human thought, especially after thought was restricted by the clergy under the rule of the Christian Church in the Middle Ages. However, with the beginning of the Renaissance and Enlightenment, philosophy began to be liberated from this control and the sciences began to become independent of philosophy, and the emergence of many philosophers. And the scholars who took upon themselves the task of liberating philosophy from all the restrictions that had controlled it throughout history; Therefore, both Francis Bacon and René Descartes try to present their own vision that serves human thought and liberates it from the restrictions of illusions, idols, and doubts that dominate or control it. In addition to that, what distinguishes the concept of the philosophy of education or educational philosophy with these philosophers is that it turned to the practical and critical side; Bacon sees education as the tool through which he can impose his control over nature to ensure the continuity of well-being or happiness for humans, or Descartes sees that education and upbringing are achieved through knowing the value of the mind. According to Descartes, reason is the fairest thing among people.